Pengaruh Harga Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Di Sudut Temu By Toastea Cafe Bogor - Madyaratri, Ardha Nareswari; Suryanti, Cecilia Valentina Srihadi; Rainanto, Bambang Hengky (Prodi Pariwisata dan LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Tourism is not only an important economic sector for a country, but also has a significant impact on the food and beverage industry. Despite facing the challenges of the Covid-19 pandemic, this industry continues to grow, showing that the need for food and beverages remains high among the community. This high demand drives the growth of businesses in the food and beverage sector, such as restaurants and cafes, creating many food and beverage businesses. In facing this competition, every entrepreneur needs to have a unique strategy to attract customers. The purpose of this study was to identify the effect of price and service quality on customer satisfaction at Sudut Temu By ToasTea Cafe Bogor. This study uses a quantitative approach, with data analyzed using SPSS Statistics 29 Year 2023. The sample of this study consisted of 100 respondents, using the probability sampling method with the Slovin formula. The instrument used was a questionnaire to collect data from respondents. The results of the study showed that price and service quality had a positive and significant effect on customer satisfaction partially. Regression analysis also showed that price and service quality had a positive and significant effect simultaneously on customer satisfaction. The most dominant variable in influencing customer satisfaction in this study was service quality. Keywords: Price, Service Quality, Customer Satisfaction